Separation of systems based on uranium hexafluoride on some halogen fluorides; Journal of Fluorine Chemistry; Vol. 130, iss. 1 - Ostvald R. V. Roman Vyacheslavovich; Shagalov V. V. Vladimir Vladimirovich; Zherin (Gerin) I. I. Ivan Ignatyevich; Amelina G. N. Galina Nikolayevna; Usov V. F.; Rudnikov A. I.; Gromov O. V. (2009, 2009)
The purpose of this paper is to present the results of the comprehensive study of the phase equilibriums liquid-solid and liquid-vapour in binary and ternary systems, formed by uranium hexafluoride, bromine trifluoride and iodine pentafluoride. Investigation of the phase equilibriums in condensed systems is done by methods of differential thermoanalysis and visual polythermal analysis. All systems belong to simple eutectics; formation of the compounds is not detected. For all systems under investigation diagrams of the phase equilibrium liquid-solid are plotted. Phase equilibriums liquid-vapour in studied systems were studied by statistical method. All systems are non-aseotropic. The article presents diagrams of the phase equilibrium liquid-vapour in binary systems, pressure of the saturated vapour dependences on liquid composition, surface of the boiling liquid and lines of the constant content of uranium hexafluoride and iodine pentafluoride in vapour phase of the ternary system UF6-BrF3-IF5.